Comparative Metabarcoding Analysis of Gut Microbiome in Wild and Captive Stump-Tailed Macaques (Macaca arctoides) - Nur Azimah, Osman; Mohd Ridwan, Abd Rahman; Millawati, Gani; Kayal Vizi, Karuppannan; Muhammad Abu Bakar, Abdul Latiff; Nor Aifat, Rahman; Badrul Munir, Md Zain (John Wiley & Sons Ltd, 2025)
The primate gastrointestinal tract is home to bacteria, which may be associated with its habitat. In Malaysia, wild stump-tailed macaques (Macaca arctoides) are found solely in the northern region of Peninsular Malaysia. No information is currently available regarding the intestinal microbiota of wild or captive Malaysian stump-tailed macaques. In this study, a fecal metabarcoding approach was utilized to determine the gut microbiome composition of wild and captive M. arctoides and how these microbial communities respond to the host's external environment. To elucidate these relationships, 16S rRNA was amplified and sequenced using the MiSeq platform, with 300 paired-end sequences. We identified 18 phyla, 38 orders, 46 families, 76 genera, and 131 species in the stump-tailed macaque samples. The most prevalent bacterial families in the gut of M. arctoides were Firmicutes (4.69%), Spirochaetes (2.87%), and Proteobacteria (2.40%). Our analysis did not reveal any substantial differences between the habitat environment and gut microbiome composition in M. arctoides. Nonetheless, to the best of our knowledge, this study is the first to document the gut microbiome of the wild M. arctoides population in Peninsular Malaysia. Future studies are required to explore and better understand potential zoonotic pathogens harbored in stump-tailed macaques.